THE EFFECT REPLACEMENT OF OXYGEN ON TRANSPORTATION SEEDS GROUPER WITH CLOSED SYSTEM - Suko Ismi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
The location of grouper aquaculture are usually far from the seed source so it takes a long time to transport the seeds. The research purposes was to extend the time by replacing oxygen so the seeds can reach the destination that is located far away with high survival and healthy condition. Previously conducted preliminary research that is transportation with a different length of time 24 hours; 36 hours; 48 hours and 60 hours. The best results of the preliminary study are 24 hour transport which is then used in the main research. In the main study, fish seeds were transported for 24 hours later, oxygen was replaced by: oxygen in disposable plastic bags replaced with new oxygen. Then repackaged to continue transport up to 12 hours; 24 hours; 36 hours and 48 hours. Trasportation conducted with closed system with car. Seeds used were cantik grouper hybrid seed i.e., a crossbreed between female tiger grouper (Epinephelus fuscoguttatus) and male marbled grouper (Epinephelus microdon), a size of 7.0 ± 0.54 cm, with a density of 125 fish / boxes. Grouper seeds were packed with 0.8 mm thick plastic bags, 120cm x 53cm wide, filled with 10 liters of sea water, oxygen is added with a volume ratio of water: oxygen is 1: 3, then put in 75 x 40 x 30 cm styrofoam box. The best result is after fish is transported 24 hours, then replaced oxygen and transported again for 24 hours, so that transportation time can be extended up to 48 hours, with survival rate 98.4%. Keywords: grouper seeds, oxygen replacement, transportation